2010
DOI: 10.1111/j.1365-3016.2010.01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and distribution of pathogens in early-onset neonatal sepsis in the era of antenatal antibiotics

Abstract: In 2001 France issued a new set of guidelines for the use of antenatal antibiotics (AA). These guidelines recommended intrapartum antimicrobial prophylaxis (IAP) to prevent group B streptococcal (GBS) disease and AA to prolong pregnancy in the event of preterm premature rupture of membranes (AA for PPROM). This study aims to determine the effects of AA, recommended by national guidelines, on the incidence and distribution of pathogens in early-onset neonatal sepsis (EONS). We performed a population-based, pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 38 publications
4
50
0
3
Order By: Relevance
“…3 Other recent data from single centers described an overall incidence of EONS of 2.07 cases per 1000 live Early-onset neonatal sepsis in Canada M Sgro et al births in Boston, 15 whereas in a French population the incidence was 1.19 per 1000 births. 16 However, this discrepancy is likely a result of the fact that ours is based solely on admissions to level 3 NICUs, rather than including a birth cohort.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…3 Other recent data from single centers described an overall incidence of EONS of 2.07 cases per 1000 live Early-onset neonatal sepsis in Canada M Sgro et al births in Boston, 15 whereas in a French population the incidence was 1.19 per 1000 births. 16 However, this discrepancy is likely a result of the fact that ours is based solely on admissions to level 3 NICUs, rather than including a birth cohort.…”
Section: Discussionmentioning
confidence: 88%
“…16 However, this discrepancy is likely a result of the fact that ours is based solely on admissions to level 3 NICUs, rather than including a birth cohort.…”
mentioning
confidence: 88%
“…Joseph et al [21] observed an increase in the proportion of infections caused by ampicillin-resistant E. coli in the period between 1988 and 1993 (67%) compared to the earlier period between 1982 and 1987 (25%) which was concomitant with the fact that in the second period 61% of the mothers received intrapartum ampicillin in contrast with the first period when only 17% received this therapy. Terrone et al [22], Bizarro et al [17] and Kunh et al [23] found a possible association between antenatal antibiotic treatment, prolonged antepartum exposure to ampicillin and infection with ampicillin-resistant E. coli . However, there are also several studies that have demonstrated that this relationship does not exist [20].…”
Section: Discussionmentioning
confidence: 99%
“…We also gathered data on potential explanatory variables (ie, variables that might explain variance in incidence or risk of group B streptococcus; 21 Andersen et al 22 Ekelund et al 23 Kuhn et al 24 Fluegge et al 25 Berardi et al 26 Trijbels-Smeulders et al 27 van den Hoogen et al 28 Hasseltvedt et al 29 Hajdu et al 30 Neto et al 31 Janek et al 32 Carbonell-Estrany et al 33 Lopez Sastre et al 34 Andreu et al 35 Persson et al 36 Heath et al 37 Oddie et al 38 Weisner et al 39 Vergnano et al 40 Subtotal (I 2 =98·6%, p=0·000)…”
Section: Data Extractionmentioning
confidence: 99%